Desenvolvimento e validação de metodologia analítica do extrato e micropartículas obtidas de Erythroxylum suberosum (Erythroxylaceae) St.-Hil. - Rodrigues, Alessandro Bastos (2017)
The genus Erythroxylum, with about 230 species is the only one represented in the Neotropical region. Species belonging to this genus have anti-inflammatory and antibacterial properties, central nervous system and hepatoprotective stimulants such as E. coca and E.catuaba, respectively. Thus, the object of this research is the species Erythroxylum suberosum A. St.-Hil. Which is a native plant used in folk medicine as for its anti-inflammatory properties. Previous studies have identified the presence of flavonoids, terpenes and alkaloids in this species, arousing the interest for the validation of analytical methodology to quantify the marker and to contribute to the use of E. suberosum extract as a vegetable derivative as a possible vegetable raw material. In this context, the present work had as objective to validate analytical methodology of quantification of rutin marker in the crude extract and dry extract of Erythroxylum suberosum A. St. Hil. (Erythroxylaceae), as well as to develop a microencapsulated vegetable derivative by spray drying. In the pharmacognostic characterization of the plant drug, leaf powder had a moisture content of 7.04%, ash content 10.49%, and a 0.8% foreign material. In the validation of routine quantification by CLAE-DAD in the extract parameters of specificity, selectivity, linearity, precision, accuracy and robustness were evaluated, demonstrating the efficiency of the methodology used. The yield of the dry extract was 11.91%. In obtaining the encapsulated spray drying derivative for microparticle formation was tested using maltodextrin drying adjuvants at concentrations of 0.32%; 0.64%; 1.60%; 3.2% and 4.8% resulted in a decrease in rutin content as the mass of maltodextrin was increased. Photoestability tests of the extracts were performed and it was found that the rutin as well as the plant extracts are stable at the incidence of light. In the characterization of the microparticles by scanning electron microscopy the formation of spherical particles of smooth and rough surface was observed, characteristic of the heat action provided in the atomization process, as well as inherent to the use of maltodextrin. This work gathered important pharmacognostic and pharmacotechnical information for the species in question, as well as for the future study of other Cerrado species.